Featuring Capability: How Carmakers Organize to Deploy Innovative Features across Products1. Issue 1 (7th October 2013) - Maniak, Rémi; Midler, Christophe; Beaume, Romain; von, Felix
<x xml:space="preserve">Abstract</x> Innovative features such as hands‐free car entry and ignition systems, stop‐start devices, telematics systems, and panoramic windshields are increasingly important to carmakers' innovation strategies. However, while product‐centric innovation has been extensively studied, there is less insight into the way companies implement their feature‐innovation strategies. The capability to explore, integrate, and deploy such attractive features is a critical dynamic capability; it allows carmakers to refresh their products, develop their competences, and maintain the efficiency of their traditional new product development. This research investigates the structures and processes of feature innovation in the automotive industry. It is based on a global investigation encompassing 9 generalist carmakers and 26 cases of feature innovation. The results show a clear trend, over the past decade, toward a structure of autonomous "advanced engineering" units and processes that are responsible for exploring innovative features and transferring them to multiple products. This paper details the key attributes of these units, and the role they play along the multiproduct learning cycle. Supplementing this structural analysis, the paper also identifies the coordination patterns between exploration and new product development activities. These results provide industry‐level insights into the way firms organize their feature‐innovation capability, and bring empirical elements to the ambidexterity literature.